Does Music Influence Stress in Mechanically Ventilated Patients? - Chlan, Linda L. (2012)
OBJECTIVES: Mechanically ventilated patients experience profound stress. Interventions are needed to ameliorate stress that does not cause adverse effects. The purpose of this study was to explore the influence of music on stress in a sample of patients over the duration of ventilatory support. RESEARCH METHODOLOGY/DESIGN: Randomized controlled trial randomized patients (56.8 ± 16.9 years, 61% male, APACHE III 57.2 ± 18.3) receiving ventilatory support to: 1) patient-directed music (PDM) where patients self-initiated music listening whenever desired from a preferred collection, 2) Headphones only to block ICU noise, or 3) usual ICU care. Twenty-four hour urinary cortisol samples were collected from a sub-set of subjects with intact renal function and not receiving medications known to influence cortisol levels (n = 65). SETTING: 12 ICUs in the Midwestern United States. MAIN OUTCOME MEASURES: Urinary free cortisol (UFC), an integrative biomarker of stress. RESULTS: Controlling for illness severity, gender, and baseline UFC (29-45 mg/day), mixed models analysis revealed no significant differences among groups in UFC over the course of ventilatory support. CONCLUSION: While music did not significantly reduce cortisol, less profound spikes in UFC levels were observed but that, given the limitations of the research, this observation could have occurred merely by chance.